Synthesis, study and use of new type biologically active arsenic-organic complex compounds - Lobzhanidze, Tea (Publishing House of Lviv Polytechnic National University, 2012)
The interaction of tetra substituted arsonium iodides with zinc iodide and potassium cyanide have been studied. By using of the data of physical, chemical and elemental analysis methods the composition and structure of synthesized compounds have been established. New composite materials of multifunctional application for individual and environmental protection, based on the silicon-organic carbofunctional oligomers and obtained complex compounds have been created. It was shown that the created composites could be used as protective covers (film materials and impregnating compositions) resistant to biocorrosion and as a biologically active polymer materials for protection of archaeological and museum exhibits. Вивчено взаємодію тетра-заміщених йодидів арсенію з йодидом цинку і ціаністим калієм. За допомогою фізичного, хімічного та елементного методів аналізу встановлено склад і структуру синтезованих сполук. На основі кремній-органічних карбофункціональних олігомерів та отриманих комплексних сполук створені нові композиційні матеріали багатофункціонального призначення для охорони навколишнього середовища. Показано, що створені композити можуть бути використані як захисні покриття (плівкові матеріали та просочувальні композиції), стійкі до біокорозії і як біологічно активні полімерні матеріали для захисту археологічних та музейних експонатів.
Синтез, дослідження та використання нового типу біологічно активних арсено-органічних комплексних сполук
Keywords: arsenic salt; complex compounds; bioactivity; d10-elements; antibiocorrosive cover; миш’якова сіль; комплексні сполуки; біологічна активність; d10-елементи; антибіокорозійне покриття